2018
DOI: 10.12681/jhvms.15601
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium avium subsp. paratuberculosis by several diagnostics techniques in clinical suspected sheep

Abstract: A total of thirty sheep with clinical symptomatology of paratuberculosis (Johne’s disease) were subjected to four diagnostic techniques: histopathological examination, bacteriological culture (in faeces and tissues), polymerase chain reaction (PCR) (in blood, tissue and faecal samples) and antibody responses (ELISA). Twenty-one (70.0%) animals showed histological lesions. Bacterial culture of both faeces and tissue revealed that 2 (6.7%) and 6 (20.0%) of the 30 sheep were infected, respectively. Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Macroscopic lesions observed in clinical cases of the current study are in agreement with earlier works, where positive cases of JD were characterized by intestinal thickening associated with longitudinal and transverse mucosal corrugations (Alharbi et al, 2012) Previously, examination of tissues samples by histopathology has been reported as the most importanttool for the diagnosis of paratuberculosis in ruminants (Coelho et al, 2017). In our investigation, typical pathological lesions of the disease were observed among tissues samples from either apparently healthy or symptomatic animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Macroscopic lesions observed in clinical cases of the current study are in agreement with earlier works, where positive cases of JD were characterized by intestinal thickening associated with longitudinal and transverse mucosal corrugations (Alharbi et al, 2012) Previously, examination of tissues samples by histopathology has been reported as the most importanttool for the diagnosis of paratuberculosis in ruminants (Coelho et al, 2017). In our investigation, typical pathological lesions of the disease were observed among tissues samples from either apparently healthy or symptomatic animals.…”
Section: Discussionsupporting
confidence: 92%
“…Detection of serum antibodies using ELISA test is the most frequently used technique for serological diagnosis, estimation of prevalence and screening of domestic animal's populations for paratuberculosis control programs (Coelho et al, 2017). Previously, it has been reported that the sensitivity and effectiveness of ELISA was low due to its inability to detect early positivity (Nielsen and Toft, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Villous atrophy, necrosis and hyperplasia of Peyer's patches have been reported by Coelho et al [87]. Histopathological changes of MLN and ICLN include infiltration of epithelioid cells and macrophages containing acid-fast organisms [82,87]; also, occasionally, giant cells and foci of caseous necrosis can be seen [88].…”
Section: Pathologic Changes Of Ptb In Sheepmentioning
confidence: 99%
“…Changes in the caecum and colon are less severe than in the terminal ileum [ 40 , 86 ]. Mesenteric and ileocaecal lymph nodes (MLN and ICLN) are enlarged in up to half of cases and are usually oedematous [ 77 , 87 ]. The histopathological characteristics observed in sheep consist of granulomatous enteritis with marked cellular infiltrate composed of epithelioid, lymphocyte, macrophage and giant cells with acid-fast bacilli [ 85 , 86 , 87 ].…”
Section: Pathologic Changes Of Ptbmentioning
confidence: 99%
“…Ωστόσο, η ευαισθησία της συγκεκριμένης μεθόδου είναι υψηλότερη συγκριτικά με άλλες ορολογικές δοκιμές, και για τον λόγο αυτόν χρησιμοποιείται σε πολλές περιπτώσεις για την ανίχνευση φορέων του ΜΑΡ (Gwozdz et al, 2000;Jungersen et al, 2012;de Silva et al, 2013;Singh et al, 2014). (Garrido et al, 2000;Bhide et al, 2006;Coelho et al, 2008Coelho et al, , 2017. Επιπροσθέτως προτείνεται η χρήση της γενετικής περιοχής f57 (Timms et al, 2011;OIE, 2014 (Liandris et al, 2009;Taka et al, 2013).…”
Section: δοκιμή της Ifn-γunclassified